(3Sff GdfSGFis - (3GdfSGFj , CMeO Hf Ydj Hf TYjH Hf Ydj Hf SfGf Hf HMQ Hf OjfGQ GdfSGFj, CHh YHO GdQMef,J (B303 (3g` s ((3bQWHI s)
(3ChdgG (B:s
(3jHJOF HChd JHQFI Cgd GdOe ai GdbSGeI s
(3BNQgG (B:s
(3jfJgi HChdcJGH jhe hdjdI ef GdSff (B( (3PcQ eG cGf GdfHi Ydjg GdSdGe jbhd EPG CUHM (B) s
(3YdjgG NWhW YdeGA GdMOjK cGdSNGhi hGHf GdTeS GdeGdci hYHO GdQMef GdbdbTfOi hbQCgG Ydi GHf MLQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B244s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1006s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs